Proceedings of the 2016 6th International Conference on Advanced Design and Manufacturing Engineering (ICADME 2016) 2016
DOI: 10.2991/icadme-16.2016.66
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of 18Ni-300 Maraging Steel Fabricated by Selective Laser Melting

Abstract: High-strength 18Ni-300 maraging steel parts were fabricated by selective laser melting (SLM) additive manufacturing. Aging treatment at 490 ºC for 6 hours was applied for improving the mechanical properties of SLM fabricated parts. The microstructure and properties of the as-fabricated SLM 18Ni-300 parts were carefully characterized and analyzed. The results show that the relatively low surface roughness, with 4.16μm for horizontal surface and 4.79μm for vertical surface, certified the high accuracy of forming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 11 publications
1
39
0
Order By: Relevance
“…The evolution mechanisms of these growth formations relate to the melt-region thermal flux direction which changes for successive layers and is theoretically explained in a recent study by Tan et al [30]. Assisted by rapid cooling rates (circa 10 3 to 10 8 K.s −1 ), these very fine cellular formations orientate themselves concurrent with the direction of heat flow/removal [29,27,26,33,23,34]. Interestingly, other research [27,47] has failed to identify any dominant crystallographic or fibre texture with a preferred grain growth orientation from the AM processed alloy.…”
Section: As-built Microstructurementioning
confidence: 94%
See 2 more Smart Citations
“…The evolution mechanisms of these growth formations relate to the melt-region thermal flux direction which changes for successive layers and is theoretically explained in a recent study by Tan et al [30]. Assisted by rapid cooling rates (circa 10 3 to 10 8 K.s −1 ), these very fine cellular formations orientate themselves concurrent with the direction of heat flow/removal [29,27,26,33,23,34]. Interestingly, other research [27,47] has failed to identify any dominant crystallographic or fibre texture with a preferred grain growth orientation from the AM processed alloy.…”
Section: As-built Microstructurementioning
confidence: 94%
“…Recently, Monkova et al [17] examined the tensile properties of EOS MS1 fabricated at 0 • , 45 • , and 90 • , and contrary to the EOS published MDS [11] they observed no significant orientation dependence in the tensile stress-strain behaviour for as-built, solution heat-treated (1h at 820 • C), and aged (6h at 490 • C) material. Other available test-data is mainly limited to static testing (tensile, and/or hardness) of maraging steel 300 fabricated in one [19,14,7,20,6,21,22,3,23,24], or two [25,26,12,16,27] of the primary AM build orientations. The most comprehensive of these studies in terms of the reported mechanical properties is [7], which monitors the effect of an array of aging heat-treatments on the static properties of AM fabricated maraging steel 300.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important properties are very high hardness, good weldability, high ductility, and easy machinability after solution annealing. Spatial stability during aging is one more positive feature of the maraging steels [8][9][10][11][12][13]. Their properties and range of applications are one of the reasons for the interest in their production by using modern technologies, including 3D printing.…”
Section: Introductionmentioning
confidence: 99%
“…The typical low-magnification microstructure of maraging steel 300 has a complex appearance, with bundled interconnections of fan-shaped solidification cells between molten lines [17,45]. An example of the sectioned microstructure is shown in Figure 4.…”
Section: Microstructurementioning
confidence: 99%